2013
DOI: 10.1097/ruq.0b013e3182817b57
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Tortuosity Causing False Positives in Detecting Renal Artery Stenosis on Doppler Ultrasound

Abstract: This study demonstrates a high false-positive rate (94%) when the PSV is in the mid-main renal artery. We suspect this pattern is due to the tortuous mid-main renal artery causing falsely elevated velocities that meet criteria for RAS. Fibromuscular dysplasia may also produce the same pattern and should be distinguished from vessel tortuosity. If the false-positive rate of Doppler ultrasound can be decreased, fewer patients will be subjected to an unnecessary follow-up study and possibly invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…We believe the increased velocity to be attributable to the tortuosity of the measured ICA. Indeed, vessel tortuosity producing falsely elevated velocities increases the false-positive rate for stenosis on Doppler ultrasound [12], [17]. The color Doppler presented here (ICA) is devoid of color aliasing and color bruit artifact in surrounding tissue which are further signs of high grade stenosis [12].…”
Section: Discussionmentioning
confidence: 91%
“…We believe the increased velocity to be attributable to the tortuosity of the measured ICA. Indeed, vessel tortuosity producing falsely elevated velocities increases the false-positive rate for stenosis on Doppler ultrasound [12], [17]. The color Doppler presented here (ICA) is devoid of color aliasing and color bruit artifact in surrounding tissue which are further signs of high grade stenosis [12].…”
Section: Discussionmentioning
confidence: 91%
“…Most studies reported sensitivity (n = 24/25) 3,5,12,14,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and specificity (n = 24/25). 3,5,12,14,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]40,41,43,44 Nine of 24 studies reported exclusively high sensitivity (range: 90%-100%) 29,33,34,37,…”
Section: Dus Versus Other Angiography Techniquesmentioning
confidence: 99%
“…Esse grupo de estudo sugere a realização do corte coronal de forma rotineira, como uma técnica adicional aos cortes transverso e longitudinal. 153,161,162 Deve-se salientar que o diagnóstico da EAR é feito principalmente pela avaliação direta, com a visualização das artérias renais em suas origens e, sempre que possível, em toda a sua extensão. Devem-se utilizar a imagem bidimensional e o mapeamento de fluxo em cores, com aquisição da velocidade de pico sistólico (VPS) e da velocidade diastólica final (VDF), que devem ser interrogadas também em qualquer ponto que sugira elevação da velocidade pelo Doppler colorido.…”
Section: Indicações Para Investigação Da Estenoseunclassified